Investigation of Langdon effect on the stimulated backward Raman and Brillouin scattering. (10th November 2021) - Qiu, Jie; Hao, Liang; Cao, Lihua; Zou, Shiyang
Abstract: In a laser-irradiated plasma, the Langdon effect makes the electron energy distribution function tend to a super-Gaussian distribution, which has important influence on laser plasma instabilities. In this work, the influence of a super-Gaussian electron energy distribution function on the convective stimulated backward Raman scattering and stimulated backward Brillouin scattering is studied systematically for a wide range of typical plasma parameters in the inertial confinement fusion. Distinct behaviors are found for stimulated Raman scattering and stimulated Brillouin scattering in the variation trend of the peak spatial growth rate and the corresponding wavelength of the scattered light. Especially, the Langdon effect on the stimulated Brillouin scattering in plasmas with different ion species and isotopes is analyzed in detail, and the parameter boundary for judging the variation trend of the peak spatial growth rate of stimulated Brillouin scattering with the super-Gaussian exponent is presented for the first time. In certain plasma parameter region, it is found that the Langdon effect could enhance stimulated Brillouin scattering in mixed plasma, which may attenuate the improvement in suppressing stimulated Brillouin scattering by mixing low-Z ions into the high-Z plasma. The comprehension of Langdon effect on stimulated Raman scattering and stimulated Brillouin scattering would contribute to a better understanding of laser plasma instabilities in experiments.